Good manners (adab) before knowledge: the true mark of excellence - Alias, Fadzilawani Astifar; Mahlan, Siti Balqis; Shamsuddin, Maisurah; Hamat, Muniroh (Unit Penerbitan JSKM, 2025)
This study looks at how being smart and having good manners (adab) are both important for students. Today, many students achieve high marks, but some still exhibit negative behavior such as rudeness and a lack of respect. This research aims to find out how students who excel academically but lack good manners often face challenges in communication, emotional regulation, and group work. The study shows that students should not only be intelligent in class but also possess strong character. A balance between knowledge and good behavior is essential to becoming a truly successful student in today’s world. Additionally, this study emphasizes the importance of character education in schools, suggesting that academic excellence alone does not guarantee lifelong success. Students with strong adab are often more empathetic, responsible, and cooperative. These qualities help them build stronger relationships and contribute positively to their communities.